Kewenangan Penyidikan oleh ANKUM pada Kasus Pidana Militer dalam Menghadapi Tantangan Konflik Kepentingan Internal - Andhika Okta Syahbana (Lembaga Pengembangan Kinerja Dosen, 2024)
Criminal law enforcement in Indonesia involves different procedures between civil society and the military, especially at the investigation stage. In the military context, Law Number 31 of 1997 concerning Military Justice stipulates investigative authority involving superiors who have the right to punish (ANKUM), military police, and prosecutors. However, there is debate regarding ANKUM's authority in investigations, especially regarding professionalism and fairness, because ANKUM does not always have adequate investigative expertise. This research aims to analyze ANKUM's authority in the process of investigating military criminal cases, as well as the challenges of internal conflicts of interest that may arise. The research method used is normative juridical with an analytical and statutory approach. The research results show that ANKUM has an important role in the investigation process, including conducting preliminary examinations, receiving reports, and carrying out detentions. However, ANKUM often faces internal conflicts of interest and limitations in exercising its authority, which can affect the fairness and professionalism of the legal process. The Military Discipline Advisory and Supervision Council (DPPDM) functions to supervise and provide consideration of ANKUM's authority. This research suggests the need for stricter supervision and improvement of the functions of the DPPDM to ensure fair and professional law enforcement.